Tingkat Kepuasan Pasien Terhadap Pelayanan Anestesi Berdasarkan Rekomendasi American Society of Anesthesiologist di Rsup Dr. Hasan Sadikin Bandung - Sitanggang, Ruli Herman; Tullah, Anay; Budipratama, Dhany (Jurnal Anestesi Perioperatif, 2026)
Background: Anesthesia services are an important component of patient–centered healthcare systems. Patient satisfaction is a key indicator of anesthesia service quality. The American Society of Anesthesiologists (ASA) recommendation questionnaire has been developed to assess patient satisfaction comprehensively.Methods: This descriptive study was conducted at Dr. Hasan Sadikin General Hospital, Bandung, from December to March 2025. A total of 384 patients aged 18–60 years who underwent general or regional anesthesia and met the inclusion criteria were included. Data were collected using a validated and reliable Indonesian version of the full ASA questionnaire. The assessed domains included provision of information and consent, attention and interpersonal relationships, and management of pain and postoperative nausea and vomiting (PONV).Results: The mean patient satisfaction level was 78.11%. Most patients reported being satisfied to very satisfied with anesthesia services. The highest satisfaction was observed in informed consent (78.8%) and overall anesthesia services (79.74%).Discussion: These findings suggest that anesthesia services were generally well perceived, particularly in communication and consent processes. Effective perioperative pain and PONV management likely contributed to positive evaluations. However, satisfaction levels below 80% indicate the need for continuous quality improvement, especially in enhancing interpersonal communication and individualized care.Conclusion: Patients rated anesthesia services as good. The ASA questionnaire is a useful tool for ongoing evaluation and quality improvement of anesthesia care.